O Redirecionamento da Execução de Título Executivo Extrajudicial em Face do Companheiro do Executado Por Força da Responsabilidade Patrimonial - Vermelho, Schamyr Pancieri (2024)
The present study endeavors to scrutinize the redirection of the execution of an extrajudicial executive title the partner of the debtor who was not part to the creation of the executive instrument. The research aims to elucidate the implications and legal underpinnings of this practice, with particular emphasis on the application of property liability as a pivotal aspect within this context. To achieve this objective, the initial focus is on elucidating the concepts of the executive process and property liability, followed by an exploration of the role of liabilities within the executive process. Subsequently, the study delves deeper into the law provisions concerning the property liability of spouses and partners, as stipulated in Article 790, item IV of the Code of Civil Procedure. This culminates in the final chapter, which endeavors to draw conclusions regarding the necessity of instituting a procedural mechanism capable of safeguarding the due process rights of the defendant's companion prior to any redirection of the execution that might impinge upon their personal assets. The research methodology adopts a qualitative approach, incorporating a thorough review of pertinent literature, analysis of jurisprudential precedents, and examination of practical case studies. It has also been examined the Brazilian and Portuguese legislations. Through this methodological framework, the aim is to provide a comprehensive and nuanced understanding of the subject matter, drawing upon doctrinal perspectives and legal frameworks from both Brazilian and Portuguese jurisdictions. The significance of this research is twofold: it serves a social purpose by seeking to safeguard the fundamental rights of individuals engaged in informal relationships, while also addressing a technical lacuna within the Brazilian legal system, wherein there currently exists no procedural model capable of ensuring due process rights in instances of execution redirection against a debtor's companion who was not part to the formation of the executive title.